Expanding therapeutic opportunities for progressive uterine cancer: clinical experience - A. G. Kedrova; S. E. Krasilnikov; A. I. Berishvili; E. A. Zvezdkina (ABV-press, 2022)
The incidence of uterine cancer in Russia increased by 28.8 % over the last 10 years. This trend is partly associated with an increasing prevalence of overweight and aging of the female population. Despite the fact that uterine cancer is limited to the uterine body in 84 % of cases, searching for new treatment regimens for patients with progressive disease is still relevant because of their poor outcomes of chemotherapy and high mortality among patients with stage III- IV cancer.The aim of this study was to present our own view on the effectiveness of lenvatinib + pembrolizumab in patients with advanced or recurrent endometrial cancer on the basis of international and own experience.The international experience with lenvatinib + pembrolizumab for advanced endometrial cancer without high microsatellite instability or impairments of DNA repair mechanisms after disease progression following previous systemic therapy showed their efficacy (38.3 %), while the effect lasting more than 6 months was observed in 69 % of cases. We report two cases of progressive uterine cancer in patients who developed complete clinical remission and demonstrated good tolerability of the therapy.